O serii Czeska Bajka wrocławskiego wydawnictwa Afera - Żygadło-Czopnik, Dorota (Przekłady Literatur Słowiańskich, 2024)
The publishing house Afera was established on the initiative of Julia Różewicz in Wrocław in 2010. The main goal of the publishing house is to introduce new Czech books to the Polish market. The Wrocław publishing house offers the Czech Fairy Tale series, within which ten positions of Czech literature for children and young people have been published. In the paper, we will consider how the Czech Fairy Tale series influences the shaping of the image of Czech literature for children and young people in Poland.